Non-syndromic monogenic male infertility - Guerri, Giulia; Maniscalchi, Tiziana; Barati, Shila; Busetto, Gian Maria; Del Giudice, Francesco; De Berardinis, Ettore; Cannarella, Rossella; Calogero, Aldo Eugenio; Bertelli, Matteo (Acta Biomedica Atenei Parmensis, 2019)
Infertility is a widespread clinical problem affecting 8-12% of couples worldwide. Of these, about 30% are diagnosed with idiopathic infertility since no causative factor is found. Overall 40-50% of cases are due to male reproductive defects. Numerical or structural chromosome abnormalities have long been associated with male infertility. Monogenic mutations have only recently been addressed in the pathogenesis of this condition. Mutations of specific genes involved in meiosis, mitosis or spermiohistogenesis result in spermatogenic failure, leading to the following anomalies: insufficient (oligozoospermia) or no (azoospermia) sperm production, limited progressive and/or total sperm motility (asthenozoospermia), altered sperm morphology (teratozoospermia), or combinations thereof. Androgen insensitivity, causing hormonal and sexual impairment in males with normal karyotype, also affects male fertility. The genetic causes of non-syndromic monogenic of male infertility are summarized in this article and a gene panel is proposed.